Lieutenant Spaulding diary - Spaulding, Lieutenant
Diary (1758 July 30-November 2 passim) describing events at Lake George, N.Y., during the French and Indian War.
Positive photocopy and negative microfilm produced with the permission of C. Brown Smith.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: George, Lake (N.Y. : Lake); New York (State) -- History -- French and Indian War, 1754-1763.; United States -- History -- French and Indian War, 1754-1763.; Army officers